2019
DOI: 10.1590/1982-3533.2019v28n2art06
|View full text |Cite
|
Sign up to set email alerts
|

A indústria brasileira no período 2007-2014: perdas e ganhos num ambiente de baixo crescimento*

Abstract: Resumo Este artigo exibe um panorama geral das transformações ocorridas na Indústria brasileira no período 2007-2014 e faz a análise de tais mudanças. A base de dados utilizada é a Pesquisa Industrial Anual - Empresa, do IBGE. No período investigado, verificou-se um avanço importante da Indústria extrativa na estrutura industrial brasileira, seja de acordo com as variáveis Valor da produção e Valor da transformação industrial, seja pelo Investimento. Destacou-se o crescimento da atividade de Extração de petról… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 3 publications
0
8
0
4
Order By: Relevance
“…3,4 Studies highlight that 20 out of 150 Brazilian ceramics end their activities in the years 2014 to 2019, which corresponds to almost 15% of the sector's companies in the region. 4,5 The same type of crisis was observed in ceramics from other countries around the world, such as Spain, 6,7 the United Kingdom, 8 and Malaysia. 9 In the state of Rio de Janeiro, there is a strong pole of red ceramics which, 10-12 like the rest of the country, felt the problems of the Brazilian economic crisis and began to present…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…3,4 Studies highlight that 20 out of 150 Brazilian ceramics end their activities in the years 2014 to 2019, which corresponds to almost 15% of the sector's companies in the region. 4,5 The same type of crisis was observed in ceramics from other countries around the world, such as Spain, 6,7 the United Kingdom, 8 and Malaysia. 9 In the state of Rio de Janeiro, there is a strong pole of red ceramics which, 10-12 like the rest of the country, felt the problems of the Brazilian economic crisis and began to present…”
mentioning
confidence: 71%
“…As a result of this event, many companies specializing in red ceramics went bankrupt or started to present financial problems 3,4 . Studies highlight that 20 out of 150 Brazilian ceramics end their activities in the years 2014 to 2019, which corresponds to almost 15% of the sector's companies in the region 4,5 . The same type of crisis was observed in ceramics from other countries around the world, such as Spain, 6,7 the United Kingdom, 8 and Malaysia 9 …”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The results obtained here for manufacturing are in line with the previous evidence obtained by Costa and Biderman (2016) for Brazil in the period from 1991 to 2011: the mean reversion effect acted in the direction of deconcentration, when less industrialized regions in the initial period grew faster than the national average However, new and different evidence was obtained for the second interval (2009--2014): even with the mean reversion effect acting to reduce the concentration index, industry became slightly more concentrated in Brazil, with a slight increase of G (5%) And this increase resulted from the predominance of the random effect (11 35%) over the reversion effect (-6 29%), with the former effect having almost twice the magnitude Despite these results, we stress that the dividing line in the two periods was marked by the start of a global economic crisis, beginning in 2008 in the United States, and by changes in the performance of the Brazilian economy The year 2009 was noteworthy for a decline of 0 3 percentage point 13 in the country's GDP growth, which fell to the lowest level since 1992 According to Oreiro and Feijó (2010), the industrial trade defi cit increased between 2004 and 2009 According to Barbosa Filho and Pessoa (2014), this downturn in Brazil's economy was the result of lower total factor productivity in the country, speciality from capital Further according to the authors, this was due more to changes in the internal economic policies adopted in this period than to external factors In fact, Fligenspan (2019) showed that between 2007 and 2014, the industrial productivity reached one of its lowest levels in 2009…”
Section: Manufacturing Industrymentioning
confidence: 99%